MOTHERHOOD, CARE, AND ONCOLOGY: AN EXPERIENCE REPORT - dos Santos Nobre, Gabriela; Santos Barbosa, Evelly Maria; Gomes Lopes, Fernanda (Cadernos ESP, 2025)
The diagnosis of childhood cancer imposes significant disruptions on family life, with mothers frequently assuming an intense and often invisible caregiving burden. This experience report aims to describe and analyze this maternal experience, seeking to broaden the discussion on gender, work, and mental health within this context. The qualitative methodology employed participant observation and focus groups with mothers at a philanthropic support home. The results highlighted exclusive dedication, strong identification with the caregiver role, and the invisible labor dimension. The discussion delves into gender asymmetry in care, the internalization of the "maternal instinct," financial dependence, and the suffering from unrecognized symbolic grief. Furthermore, a scarcity of self-care practices was observed. It is concluded that this form of motherhood is a solitary and exhaustive function, demanding renunciations and calling for social recognition and supportive public policies.